Rethinking EU external migration policy: contestation and critique. Issue 3 (27th May 2019) - Oliveira Martins, Bruno; Strange, Michael
ABSTRACT: The externalization of the EU's migration policies has seen a sharp increase in recent years but many aspects of its historical roots, internal dynamics, and broader implications remain insufficiently explored. This special issue analyses recent developments in the EU's external migration policies including the extra-territorial reach of EU migration policies; the power relationships between the EU and third countries involved in EU migration policies; the overlap with critical development studies and post-colonialism; the replication of many of Australia's external migration policies; the impact of EU external migration policies on third countries, and civil society contestation of those policies. As the contributions show, the series of policies discussed here go beyond the specific empirical area of migration control to have significance for both the future of the European Union and its role in global affairs.